Don’t Reinvent the Wheel. Spin it for Advocacy - Knipe, Robert (Strategies, 2020)
This article expands previous recommendation to “be proactive” by providing practical examples that have the potential to encourage stakeholders to value HPE programs before these programs are threatened with reduction or elimination. The aim is to capitalize on positive aspects of programs that are already in place to maximize publicity within communities.
_eprint: https://doi.org/10.1080/08924562.2020.1805941
Keywords: dept.hms; peer-reviewed

Physical activity used as punishment: advocating for better practices - Paulson, Lisa; Knipe, Robert (Journal of Physical Education, Recreation & Dance, 2023)
SHAPE America (2021) contends the use of physical activity used as punishment and/or behavior management as an inappropriate practice. The position statement acknowledges both the administration and withholding of physical activity as punishment, however, this paper focuses on the use of exercise as punishment (EAP) in physical education settings. While deemed inappropriate, the use of EAP is still happening today (Barney et al., 2016). The purpose of this viewpoint paper is to encourage appropriate pedagogies and practices while increasing awareness of national recommendations. Strategies for advocacy efforts are discussed.
0 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/07303084.2023.2173934
Keywords: dept.hms; peer-reviewed

Position Statements for Advocacy: Does Using Physical Activity as Punishment Make Students Leave Physical Education Wanting to Hide or Seek? - Paulson, Lisa; Knipe, Robert (Strategies, 2025)
This article explains how to use and apply the SHAPE America position statement “Physical Activity Should Not Be Used as Punishment and/or Behavior Management” in one’s own teaching and as an advocacy tool. © 2025 SHAPE America.
Keywords: dept.hms

Beyond bricks and mortar: a qualitative examination of factors influencing diffusion of an innovative PETE graduate program - Jones, Emily; Eberline, Andrew; Knipe, Robert (Curriculum Studies in Health and Physical Education, 2020)
As novel approaches to post-graduate education emerge and professional learning concepts evolve, there is a need for additional research investigating the processes by which physical education teacher education (PETE) faculty and administrators conceptualise and launch non-traditional graduate programming. The purpose of this study was to investigate stakeholders’ perceptions of the factors influencing the diffusion of a one-year, contextually based, full-immersion master’s degree in PE. Six stakeholders, including individuals from a mid-sized university, a global fitness corporation, and a rural K-12 school district all located within the United States, participated in semi-structured interviews. Deductive content analysis methods were used to analyse the data. Utilising Roger’s Attributes of Innovation, eleven sub-themes emerged. Findings represent stakeholders’ perceptions of facilitators and barriers to the implementation and diffusion of an innovative effort to deliver graduate education. Challenges and lessons learned provide insight for PETE faculty and administrators seeking to expand graduate education beyond bricks and mortar.
_eprint: https://doi.org/10.1080/25742981.2020.1719853
Keywords: Physical education teacher education; collaboration; dept.hms; graduate education; innovation; peer-reviewed; practice-to-theory

State Physical Education Policy Changes From 2001 to 2016 - Dauenhauer, Brian; Keating, Xiaofen; Stoepker, Peter; Knipe, Robert (Journal of School Health, 2019)
ABSTRACT BACKGROUND State policies influence the quantity and quality of educational programs delivered in schools. This study examined state physical education policy changes from 2001 to 2016 by analyzing data reported in The Shape of the Nation Report . METHODS Policies related to state mandates for physical education, time/credit requirements, assessment and fitness testing requirements, adoption of state standards, and allowance of substitutions were analyzed over 5 editions of the report using repeated measures statistics. RESULTS A majority of state physical education‐related policies have not changed over the past 15 years despite calls by numerous public health agencies for enhanced physical education in schools. There was, however, a significant increase in the number of states adopting teaching standards and requiring assessment and fitness testing in physical education, mirroring a broader shift in education toward standards, assessment, and accountability. CONCLUSIONS Despite improved rigor in physical education through the adoption of standards and assessment practices, physical education continues to be marginalized in schools by a lack of curricular time and inappropriate substitution policies. Stronger policies are needed for physical education to have a substantial impact on school health.
Keywords: dept.hms; peer-reviewed

Remote Lesson Study as Continuing Professional Development for Physical Education Teachers - Colburn, Jeffrey; Knipe, Robert; Doherty, Brooke; Stephenson, Rachyl; Hamilton, Xiaofen (Journal of Teaching in Physical Education, 2026)
Purpose: This study investigated experiences of physical education teachers (PETs) participating in online remote andragogy-based lesson study (AbLS) during a pandemic. Method: Five PETs participated in this phenomenological case study. Seventeen online AbLS collaborative meetings took place via Zoom software. Three rounds of semistructured interviews were conducted and analyzed using collaborative qualitative analysis. Results: Three themes emerged: (a) AbLS facilitated depth of learning, increasing professional and individual growth; (b) AbLS structure influenced experience; and (c) the professional community of AbLS supported a natural adult learning (andragogical) environment. Discussion/Conclusion: Remote AbLS presented benefits for these PETs beyond professional learning that prior continuing professional development had not, including a sense of community, belonging, and professional worth. AbLS may have implications for research in perceived mattering and continuing professional development facilitation for PETs. Remote AbLS may bolster PETs in challenging local learning communities. © 2026 Human Kinetics, Inc.
Keywords: andragogy; dept.hms; marginalization; professional learning; remote communities

Preservice Physical Education Teacher Attitudes Toward Fitness Tests and the Factors Influencing Their Attitudes - Stephenson, Rachyl; Hamilton, Xiaofen; Liu, Xiaolu; Hodges, Michael; Colburn, Jeffrey; Knipe, Robert (Physical Educator, 2022)
Keywords: dept.hms; peer-reviewed

Secondary physical education teaching methods course: through the lens of the preservice teachers - Hodges, Michael; Phelps, Ashley; Knipe, Robert; Doherty, Brooke; Colburn, Jeff; Hamilton, Xiaofen D. (Curriculum Studies in Health and Physical Education, 2023)
Public school secondary physical education needs support. One approach in assisting is to improve the next generation of preservice physical education teachers (PPETs). The purpose of the study was to explore PPET secondary physical education training through the secondary teaching methods course offered in two universities in the US. A total of 14 PPETs participated in the study. Qualitative methods were employed through a phenomenological framework. Semi-structured interviews were analyzed using constant comparative methods [Kolb (2012). Grounded theory and the constant comparative method: Valid research strategies for educators. Journal of Emerging Trends in Educational Research and Policy Studies, 3(1), 83–86]. Two themes emerged: (a) PPETs have a stronghold on management, as they displayed feelings of high importance towards this topic, and (b) preparing for quality instruction when cooperating teachers are not, resulting in PPETs’ questioning the importance of lesson planning. PPETs views on the misalignment of university and district practices are troubling and suggest university and K-12 partnerships to be formed. Future research should examine ways to improve field experiences associated with these courses.
_eprint: https://doi.org/10.1080/25742981.2022.2042340
Keywords: Secondary teaching methods courses; college physical education students; curriculum and pedagogical knowledge; dept.hms; peer-reviewed; secondary physical education teacher preparation

A Qualitative Exploration of Technology Use Among Preservice Physical Education Teachers in a Secondary Methods Course - Phelps, Ashley; Colburn, Jeffrey; Hodges, Michael; Knipe, Robert; Doherty, Brooke; Keating, Xiaofen D. (Teaching and Teacher Education, 2021)
Educational technologies have been known to positively impact teaching and learning in physical education. This rapid development of new technologies has encouraged physical education teacher education (PETE) programs to prepare preservice physical education teachers (PPETs) with experiences rooted in technological pedagogical content knowledge (TPACK). This study aimed to understand current PPET experiences with technology in a secondary methods course. A total of 14 participants from two PETE programs participated in this study. Semi-structured interviews were conducted and later analyzed using a grounded theory methodology. Two themes were discovered: (a) PPETs used technology to plan, instruct, and/or assess their secondary physical education classes, and (b) PPETs encountered barriers when using technology. Future research should examine the levels of technology understanding among PPETs.
Keywords: Assessing; Instructing; Instructional technology; Planning; Preservice physical education teacher; Secondary methods; dept.hm; peer-reviewed

Development of a Scale Measuring Chinese Preservice Physical Education Teachers’ Beliefs About the Physical Education Profession - Fan, Yao; Keating, Xiaofen D.; Liu, Jingwen; Zhou, Ke; Shangguan, Rulan; Knipe, Robert (The Asia-Pacific Education Researcher, 2018)
This project aimed to develop a valid and reliable scale measuring Chinese preservice physical education teachers’ beliefs about the physical education profession (PPET-BPEP). The domains and items were created from a conceptual analysis of the previous literature and PPETs’ responses to an open-ended survey. Six experts in the field of physical education and educational psychology evaluated the content validity of the scale. The reliability and factorial validity of the scale were examined utilizing a sample of 696 Chinese PPETs. The PPET-BPEP scale with 12 items embedded in two domains revealed acceptable content validity, internal structure validity, and internal consistency. The two domains were labeled as “sense of calling” and “value of physical education profession” based on the shared content of items in each domain. We recommend using PPET-BPEP scale for PPET recruitment and preparation. The scale can also help establish teacher belief scales in other subject matters. Future validation of the scale is needed in different countries and institutions.
Keywords: Future physical education teacher; Professional beliefs; Survey development; Validity and reliability; dept.hms

A Qualitative Examination on the Preparation of Preservice Physical Education Teachers for Assessment in Secondary Teaching Methods Courses in the Us - Hodges, Mike; Liu, Xiaolu; D. Hamilton, Xiaofen; Doherty, Brooke; Phelps, Ashley; Colburn, Jeffrey; Knipe, Robert (Physical Education and Sport Pedagogy, 2022)
Purpose: This study aimed to examine the ways in which physical education teacher education (PETE) prepares preservice physical education teachers (PPETs) to select and implement appropriate assessments.Methods: PPETs (N = 14) enrolled in the secondary teaching methods course at two US universities participated in the study. Semi-structured interviews were completed to collect data concerning how assessment knowledge and skills were taught and learned. Constant content comparison method was used to analyze the data.Results: Two major themes with varying sub-themes emerged from the data: ‘Scratching the surface of assessment with unclear learning objectives’, and ‘Perceiving the importance of assessment, but still not integrate it into instruction’ Overall, assessment was not found to conjunctionally taught with instruction. School-based field experiences pertaining to assessment content and pedagogical knowledge were also weak.Conclusions: Minimum assessment knowledge and skills were taught in secondary methods courses with little field experience pertaining to assessment. Future research is needed on examining PETE program content and pedagogy courses to highlight the need for assessment instruction and transform our approaches to preparing PPETs.
1 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/17408989.2022.2153816
Keywords: Evaluation; assessment preparation; dept.hms; peer-reviewed; physical education students; teaching methods courses